Remittance Analysis and their Economic Aspect, Kosovo Case (European Journal of Marketing and Economics, 2018)
The role of remittances as an external source of funding is considered to be extremely beneficial for many countries, especially for those facing with large number of unemployed and a slow pace of economic development. As Kosovo faces an unfavourable economic situation, remittances from abroad have been a great support, contributing to the well-being of Kosovar families. Kosovo's economy heavily relies on the remittances of immigrants living in Diaspora, but the data and analysis regarding the extent of the remittances in Kosovo have been scarce. In this paper, an analysis will be conducted on the remittances received so far in Kosovo, focusing on their effects on the economy, and especially their impact on GDP and exports and FDI. As a conclusion, this study is expected to yield results that will reflect more in detail and more precisely as to what is the real impact of remittances in emerging economies and which have a high percentage of remittances received in general in these countries, and in particular more insights will be provided as to where Kosovo stands at this level of remittance impact on the economy.
Keywords: remittances; investments; economic development; Kosovo